Evaluating the Efficiency Measurement of Malaysian Logistics Company - Sanusi, Sufia Athirah; Ramli, Noor Asiah; Shariff, S.Sarifah Radiah; Masudin, Ilyas (Semarak International Journal of Transportation and Logistics, 2025)
Logistics plays a crucial role in the smooth flow of goods, data, money, technology, and individuals along the supply chain, which in turn affects the efficiency of commerce worldwide. Thus, a company's efficiency is very important. The purpose of this research is to find the efficiency score of 14 Malaysian logistic companies while enduring the Covid 19 pandemic in 2020. Data was gathered from corporate annual reports from 2010 to 2021. 14 Malaysian logistics organizations were chosen as decision making units (DMUs) for this study. The companies' performance was evaluated using the Data Envelopment Analysis (DEA) model, Super Efficiency for input orientation. The primary findings show that companies cope very well to be consistently fully efficient. Further analysis of the results was done using the Super Efficiency model to identify the company that can be ranked as the most efficient. Due to the pandemic and the variables used as inputs and outputs for the DEA model were precisely taken from the financial statements, limits strategic analysis. The outcomes of this research are useful to aid in the evaluation of resource use and have the possibility to be used in evaluating current policies in order to guarantee that logistics businesses are efficient and sustainable.